LiNi0.5Mn1.5O4 microcubes: cathode materials with improved discharge/charge performances for lithium-ion batteries. Issue 3 (19th December 2018) - Fu, Yanli; Wu, Liqiong; Xu, Shengang; Cao, Shaokui; Li, Xinheng
Abstract : LiNi0.5 Mn1.5 O4 microcubes grown from nanowires delivered an initial discharge capacity of 123 mAh g −1 at 1C and maintained 95% of the capacity after 50 cycles due to interfacial effect. Abstract : We report uniform mesoporous LiNi0.5 Mn1.5 O4 microcubes grown from nanowires via oriented attachment. Mechanical tests show that the microcubes had excellent elongation performances. Electrochemical measurements show that LiNi0.5 Mn1.5 O4 microcubes delivered an initial discharge capacity of 123 mAh g −1 at 1C and maintained 95% of the capacity after 50 cycles.